Thermal fatigue behaviour of WC-20Co and WC-30(CoNiCrFe) cemented carbide. (November 2016) - Emanuelli, L.; Pellizzari, M.; Molinari, A.; Castellani, F.; Zinutti, E.
Abstract: Cemented carbides are used in many applications, such as drawing dies, cutting tools and hot rolls. In applications where cyclic temperature variations are present, an important factor that must be taken into account is thermal fatigue (TF). In this study, TF behaviour of two commercial cemented carbides was evaluated by means of a custom test configuration inducing a biaxial state of stress. At an early stage of the damage process, crack density is higher in WC-30(CoNiCrFe), while crack length is lower than WC-20Co. At a later stage cracking proceeds by propagation of existing cracks, partly reducing the difference between the two grades. The prevailing fracture modes are different in the two materials. In WC-20Co the main fractures occur at the WC/WC grain boundary and at WC/Co interface. In WC-30(CoNiCrFe) cracking proceeds by fracture of carbide particles and shear fracture of binder phase. A possible influence of oxidation on the TF crack propagation has been evidenced. Graphical abstract: Highlights: Transgranular/intergranular fracture of WC ratio changes, increasing the DWC . The propagation rate decreases, increasing the binder content. The oxidation rate depends mainly on the matrix amount. An oxidation induced crack propagation mechanism is confirmed.